The Second Hyper-Zagreb Coindex of Chemical Graphs and Some Applications. (15th November 2021) - Ayache, Ahmed; Alameri, Abdu; Alsharafi, Mohammed; Ahmed, Hanan
Abstract : The second hyper-Zagreb coindex is an efficient topological index that enables us to describe a molecule from its molecular graph. In this current study, we shall evaluate the second hyper-Zagreb coindex of some chemical graphs. In this study, we compute the value of the second hyper-Zagreb coindex of some chemical graph structures such as sildenafil, aspirin, and nicotine. We also present explicit formulas of the second hyper-Zagreb coindex of any graph that results from some interesting graphical operations such as tensor product, Cartesian product, composition, and strong product, and apply them on a q -multiwalled nanotorus.